PENGEMBANGAN MANAJEMEN BERBASIS MADRASAH - Abdullah Abdullah (PEDAGOGIK : JURNAL PENDIDIKAN, 2015)
Law  No.  20  of  2003  on  National  Education  System  which  mandates  that  the provision  of  education  conducted  by the  school-based  management  principles  / madrasah   is  evidence   of  seriousness   of  the  government   in  addressing   the aspirations of the people associated with the increased demands of the quality of education.  In order  to answer  the challenges  in the field  of education  and the expectations  of  society  in  the  form  of  guidance  to  improve  education  quality, school-based management / madrasah (MBS / MBM) is an absolute thing that must be addressed and implemented, because theoretically MBS / MBM no longer make the government as the central authorities of education, but occurs disenteralisasi autonomy and education in Madrasah.